2009
DOI: 10.4028/www.scientific.net/msf.618-619.513
|View full text |Cite
|
Sign up to set email alerts
|

Consolidation of Titanium, and Ti-6Al-4V Alloy Powders by Powder Compact Forging

Abstract: Consolidation of titanium and titanium alloy powders using thermomechanical powder metallurgy (TPM) processes (powder compact forging, extrusion and rolling) is one way that can lead to cost-effective production of high value-added consolidated titanium and titanium alloy products such as near-net shaped components, tubes and plates. This paper provides an overview of the quality, microstructure (to limited depth), porosity level and mechanical properties of disks produced using open die forging of powder comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 6 publications
(6 reference statements)
0
8
0
Order By: Relevance
“…[15,17] To ensure that the powder compact is fully consolidated, it is critical to ensure that strong atomic bonding is established at all or most of IPBs through diffusion bonding during PCF and PCE, and ideally they are transformed into grain boundaries or interfaces. One way of revealing whether strong atomic bonding is established at IPBs in the consolidated materials is to conduct tensile testing to facilitate formation of cavities at IPBs where atomic bonding is not established or still very weak.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15,17] To ensure that the powder compact is fully consolidated, it is critical to ensure that strong atomic bonding is established at all or most of IPBs through diffusion bonding during PCF and PCE, and ideally they are transformed into grain boundaries or interfaces. One way of revealing whether strong atomic bonding is established at IPBs in the consolidated materials is to conduct tensile testing to facilitate formation of cavities at IPBs where atomic bonding is not established or still very weak.…”
Section: Introductionmentioning
confidence: 99%
“…Khan et al [11] used high velocity powder compacting technique to compact Ti-6Al-4V (wt pct) alloy powder and found that with a high ram velocity, a relative high density of~86 pct can be achieved. Thermomechanical powder consolidation techniques such as hot isostatic pressing (HIP), [12,13] powder compact forging (PCF) [14][15][16] , and powder compact extrusion (PCE) [17] have been used by several research groups to consolidate titanium/titanium alloy powders and titanium/alloying element/master alloy powder blends. These works showed clearly that such powder consolidation processes can achieve good mechanical properties which are comparable to those of ingot metallurgy titanium/titanium alloys with same compositions.…”
Section: Introductionmentioning
confidence: 99%
“…It has great potential to form the parts with complicated internal cavities, which are difficult to be fabricated by traditional methods such as forging, machining, and so on. e NNS technology is composed of several methods: powder injection molding (PIM), hot isostatic pressing (HIP), powder forging (PF), and cold isostatic pressing (CIP)/sintering [2,3]. Usually, the products fabricated by PIM have inferior mechanical properties than those using other NNS technologies [4].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the titanium alloy airframe fabrication process for the Boeing 787 aircraft, approximately 83% of the titanium is discarded in the form of machining chips [6]. Several near-net shape (NNS) fabrication technologies (e.g., powder injection molding (PIM), hot isostatic pressing (HIPping), powder forging (P/F), additive manufacturing, and cold isostatic pressing (CIP)/sintering) have been incorporated with powder metallurgy (P/M) approaches to improve efficiency and cost [7][8][9].…”
Section: Introductionmentioning
confidence: 99%